Integrated vehicle dynamics control via coordination of active front steering and rear braking - Doumiati, Moustapha; Sename, Olivier; Dugard, Luc; Martinez-Molina, John-Jairo; Gaspar, Peter; Szabo, Zoltan (European journal of control, 2013)
This paper investigates the coordination of active front steering and rear braking in a driver-assist system for vehicle yaw control. The proposed control system aims at stabilizing the vehicle while achieving a desired yaw rate. During normal driving situations, active steering control is involved for steerability enhancement. However, when the vehicle reaches the handling limits, both steering and braking collaborate together to ensure vehicle stability. The coordination of these actuators is achieved through a suitable gain scheduled LPV (Linear Parameter Varying) controller. The controller is synthesized within the LMI (Linear Matrix Inequalities) framework, while warranting robust H∞ performances. Time and frequency simulation results show the effectiveness of the proposed control scheme when the vehicle is subject to various critical driving situations.